The association of angiotensin-converting enzyme gene polymorphism with respiratory distress syndrome in premature neonates - Razek-Midan, Dina Abdel; Abou-El-Ella, Soheir Sayed; Tawfik, Maha Atef; Konsowa, Amr (The Turkish Journal of Pediatrics, 2022)
Background. There was a contradiction in the previous literature on whether the D/D genotype of angiotensinconverting enzyme (ACE) is a protective or risk factor for respiratory distress syndrome (RDS) in premature neonates. To solve this debate, we intended to examine the association between ACE gene polymorphism and RDS in premature neonates. Methods. We enrolled a total of 100 premature neonates with gestational age below 37 weeks. They were divided into 2 groups, the case group included 50 premature neonates diagnosed with RDS. While the control group included 50 premature neonates with no signs of RDS. We assessed ACE gene polymorphism using polymerase chain reaction. All neonates underwent chest x-ray, echocardiography, and routine laboratory investigations. Results. D/D and D/I genotypes were higher in the control group (48% and 50%) than in the case group (26% and 40%). Whereas, I/I genotype was lower in the control group (2%) than in the case group (34%) (p < 0.001). By counting D alleles among members of both groups, D-alleles were significantly higher in the control group (73%) than in the case group (46%) (p < 0.001). Conclusions. In premature neonates, D/D and D/I genotypes and D-alleles are protective factors for RDS. Whereas, I/I genotype and I-alleles are associated with the incidence of RDS with complications.